Pengaruh Participatory Learning Approach (PLA) terhadap Pengetahuan dan Kesadaran Ibu dalam Pencegahan Stunting - Raju Kapadia; Nurbani Nurbani; Mita Agustina (Bima Nursing Journal, 2022)
A mother in the family has an important in fulfilling family nutrition to prevent stunting. Various methods and counseling to mothers to increase knowledge have been widely given, but most are still traditional or one-way models. The learning approach that is currently being developed is a learning model that involves an active role or maximum participation so that the learning target is more involved. Participatory Learning Approach PLA) is a method that is believed not only to increase knowledge but also increase awareness about learning materials to a deeper extent. Through a combination of lectures, demonstrations, discussions and presentations, it is hoped that there will be an increase in knowledge and awareness of mothers will be better. This study aims to identify the influence of participatory learning approach techniques in increasing maternal awareness and knowledge in stunting prevention. The research was conducted using the Quasi Experimental method, with the Pre And Post Test With Control Group Design model. Data collection was carried out through a 3S (Sehari Sadar Stunting) learning program to 50 mothers divided into two groups. The intervention group was given a one-day learning program with a Participatory Learning Approach approach, namely a combination of lectures, demonstrations, discussions and presentations.While the control group was given a joint program but with a traditional learning model.  The two groups then conducted a pre and post test looking for differences in scores through the paired t test. The results of the study obtained by the implementation of PLA were able to increase maternal knowledge about stunting with the results of paired t tests in pre-post tests increased significantly p 0.001 (p > 0.005). This method is also able to increase maternal awareness in stunting prevention measures through pregnancy screening, exclusive breastfeeding, supplemental feeding and food processing varyingly. The conclusion of this study is that the implementation of the Participatory Learning Approach method is able to increase the understanding and awareness of mothers and mothers-to-be in stunting prevention measures. The implementation of methods of increasing maternal participation needs to be improved in the form of maternal empowerment actions in stunting prevention